Sago starch hydrogel prepared through gamma irradiation and impregnated with silver nanoparticles - Eslami, Fayezeh (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Hydrogel based on petroleum polymer is expensive and non-decomposable, which makes them as heavy waste in the environment. In order to suitable environment friendly issues and global needs, this study was designed such that it focused on the production of thermosetting hydrogel based on sago starch / polyvinyl alcohol (SS/PVA) and silver nanoparticles (SNP) as wound dressing materials. However, this research concluded only on the developing materials and not elaborated for in vivo and in vitro tests. The hydrogel was prepared by blending 30, 50 and 70 w/v % of SS solution with PVA and then subjected to gamma irradiation at 15, 25 and 35 kGy. The effects of two variables (swelling properties and absorbency) with different SS content and doses of gamma irradiation were studied. The swelling ability increased by decreasing SS content and gamma irradiation doses. The highest absorbency obtained by SS/PVA hydrogel with 30 w/v % SS at 15 kGy was 1426%. The SS/PVA hydrogel with the highest absorbency was selected for impregnation with 3, 5 and 7 w/v % SNP through reduction of silver nitrate by sodium borohydride. SS/PVA hydrogels with 0, 3, 5 and 7 w/v % SNP were evaluated for functional chemical groups and morphology analysis by FTIR and SEM respectively and also for the effect of SNP on swelling properties. The results of FTIR confirmed that SNP formed inside the hydrogel by a slight shift of the peak from 1325 (pure SS/PVA hydrogel) to 1352 cm-1 (SS/PVA hydrogel with SNP) corresponding to the hydroxyl band as a hydrophilic group that can absorb water. SEM showed the evidence of SNP embedded into pure SS/PVA hydrogel. The addition of SNP free spaces appeared within SS/PVA hydrogel, which held more water than pure hydrogel. The swelling ability increased with the impregnation of SNP but decreased with the increase of SNP and temperatures. The values of equilibrium water content calculated from the water content of SNP-SS/PVA hydrogel of 93 to 94 % were greater than the present water content value of the body, which is 60%. As a preliminary study, it can be confirmed that the SS/PVA hydrogel with SNP can be used as a hydrogel for wound healing dressing.